2015
DOI: 10.1055/s-0034-1393179
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided choledochoduodenostomy vs. transpapillary stenting for distal biliary obstruction

Abstract: EUS-CDS performed by expert endoscopists was associated with a short procedure time and no risk of pancreatitis, and would therefore be feasible as a first-line treatment for patients with distal malignant biliary obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 26 publications
2
59
0
Order By: Relevance
“…One study at a tertiary care center found that EUS-BD was required by only three (0.6%) of 524 patients with a native papilla undergoing therapeutic ERCP, concluding that EUS-BD should not replace good ERCP techniques. 74 Similar results were observed in another retrospective study comparing EUS-BD and ERCP. 73 A retrospective comparative cohort study comparing the clinical efficacy and safety of EUS-CDS and ERCP as first-line treatment for distal malignant biliary obstruction in 82 patients (26 EUS-CDS, 56 ERCP) found that mean procedure time was significantly shorter with EUS-CDS than with ERCP, although their clinical success and adverse event rates were similar.…”
Section: Eus-bd Versus Ercpsupporting
confidence: 83%
“…One study at a tertiary care center found that EUS-BD was required by only three (0.6%) of 524 patients with a native papilla undergoing therapeutic ERCP, concluding that EUS-BD should not replace good ERCP techniques. 74 Similar results were observed in another retrospective study comparing EUS-BD and ERCP. 73 A retrospective comparative cohort study comparing the clinical efficacy and safety of EUS-CDS and ERCP as first-line treatment for distal malignant biliary obstruction in 82 patients (26 EUS-CDS, 56 ERCP) found that mean procedure time was significantly shorter with EUS-CDS than with ERCP, although their clinical success and adverse event rates were similar.…”
Section: Eus-bd Versus Ercpsupporting
confidence: 83%
“…The overall rate of adverse events in the EUS-HGS group is consistent with recent studies and illustrates the relatively good safety profile of EU-BD compared with ERCP, as shown by one recent study comparing the clinical efficacy and safety of EU-BD and ERCP for patients with distal malignant biliary obstruction. 30 …”
Section: Resultsmentioning
confidence: 99%
“…Although surgical drainage is also an option when minimally invasive procedures fail, to our knowledge there are no studies directly comparing the outcomes of EUS-guided and surgical biliary drainage. In a recent study, EUS-guided biliary drainage was also comparable with conventional transpapillary ERCP drainage in terms of clinical success, procedural time, and adverse events, being even associated with a lower rate of pancreatitis [7]. However, this was a small single-center study and standard ERCP has a demonstrated high efficacy and safety profile with experienced operators and should be the first-line approach to biliary drainage.…”
Section: Discussionmentioning
confidence: 93%